The Efficacy of Combination Therapy by Adalimumab with Methotrexate and of Monotherapy by Methotrexate for Children Suffering from Polyarticular Juvenile Idiopathic Arthritis - V. A. Keltsev; L. I. Grebyonkina; Ye. D. Moiseeva ("Paediatrician" Publishers LLC, 2016)
Background: The use of genetically engineered biological agents in patients with juvenile idiopathic arthritis (JIA) allows to achieve good results in treatment. However, their efficacy in patients refractory to basic antirheumatic drugs, requires further analysis.Objective: To study the efficacy and safety of the combination therapy by adalimumab with methotrexate and of the monotherapy by methotrexate in children with JIA.Methods: It was conducted a perspective (annual) comparative research with the analysis of the results of treating children with polyarticular seronegative JIA refractory to basic immunosuppressive therapy. The efficacy was assessed by ACRpedi criteria and by dynamics of values of cellular and humoral immunity indicators. Safety was determined by the number of adverse effects.Results: The combination therapy by methotrexate with adalimumab for children with JIA (n = 14) in a shorter time than the monotherapy by methotrexate (n = 17) induced arthritis remission. After 46 weeks of treatment, the remission of arthritis and the normalization of laboratory findings were reported in 6 (43%) patients treated by adalimumab with methotrexate, and in 3 (18%) children - methotrexate (p = 0.233); adverse effects - in 4 (29%) and 14 (82%) cases (p = 0.004), respectively. No serious adverse effects have been registered.Conclusion: The prescription of adalimumab in combination with methotrexate in children with JIA, refractory to basic immunosuppressive therapy, allows to achieve rapid remission of the disease while preserving the effect in a significant number of patients within 46 weeks of therapy.